Jurnal Perancangan Aplikasi Pencatatan Piutang Usaha bagi UMKM dalam Mendukung Efisiensi - Shifa Sihatul Iman; Destian Arshad Darulmalshah Tamara; Leni Nur Pratiwi (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Bucrak Production is one of the UMKM in Bandung City which is engaged in the production of drum musical instruments which are then sold to artists. This UMKM applies manual recording, causing the presentation of information to be slow and inaccurate. To create a business recording application and apply it to Bucrak Production. This research was carried out in stages starting from field studies, problem formulation, research objectives setting, data collection and analysis aimed at knowing the weaknesses and needs of the currently applied system. The next stage is to design the next system based on information from the previous stage, the implementation of the application that has been made will be carried out. The last stage is making conclusions. The results of this study note that there are many records in Bucrak production that need to be developed. Recording of notes which is done manually and in archiving the recording documents is not archived properly so that the information presented is not complete and accurate. The result is not being able to find out receivables per debtor that takes a long time. The application is designed in such a way that it is easy to use and is used in recording so that it can present information quickly and accurately. Keywords: